Cyclization of Gold Acetylides: Synthesis of Vinyl Sulfonates via Gold Vinylidene Complexes1. Issue 15 (5th March 2014) - Bucher, Janina; Wurm, Thomas; Nalivela, Kumara Swamy; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract Differently substituted terminal alkynes that bear sulfonate leaving groups at an appropriate distance were converted in the presence of a propynyl gold(I) precatalyst. After initial formation of a gold acetylide, a cyclization takes place at the β‐carbon atom of this species. Mechanistic studies support a mechanism that is related to that of dual gold‐catalyzed reactions, but for the new substrates, only one gold atom is needed for substrate activation. After formation of a gold vinylidene complex, which forms a tight contact ion pair with the sulfonate leaving group, recombination of the two parts delivers vinyl sulfonates, which are valuable targets that can serve as precursors for cross‐coupling reactions, for example.